Knowledge and awareness about chronic kidney disease among undergraduate students in International Islamic University Malaysia Kuantan Campus - Sowtali, Siti Noorkhairina; Aminuddin, Ali; Mohd Shah, Azarisman Shah; Mohd Yusoff, Dariah; Draman, Che Rosle; Sakinah, Harith; Mohd Nawi, Nur Izzati; Mohd. Zuki, Nurul Atikah; Zainol, Alia Jasmin (Universiti Sains Malaysia, 2019)
Chronic kidney disease (CKD) causes 70% of all death globally. The prevalence of CKD has shown an increasing trend for the past 20 years in Malaysia. Thus, determining the knowledge and awareness of CKD among healthcare students in preparing them to be a good healthcare provider in the future is important. This study aimed to determine the association between knowledge and awareness about CKD among International Islamic University Malaysia (IIUM) undergraduate students. A crosssectional study was conducted among 108 students using simple random sampling method. The questionnaire was given to the class representative to be self-administered to interested students. It had close-ended questions consisting of Part A to Part D. The scoring given for correctly answered items was one and the total score for Part C was 7 marks. Most of the students were female (70.4%). The mean knowledge score of CKD was 3.65 (SD = 1.12) with nearly half of the students (43.5%) classified as having poor knowledge. Most respondents were aware about CKD (99.1%) and have heard about it from medical personnel (48.1%) and the Internet (25.9%). Further analysis showed that only courses taken by the respondents were significantly associated with knowledge on CKD (p = 0.039). The level of knowledge among undergraduate students is still poor, yet they are aware about the existence of CKD and its aetiology. Therefore, the health sciences curriculum should emphasise on CKD management from a multidisciplinary aspect of care. It is recommended to conduct similar research among different student populations to create awareness and obtain important baseline findings.